NUTRIENT INTAKE OF WEST AFRICAN DWARF GOATS FED DIETARY MODELS OF ENSILED CASSAVA PEEL MEAL FORTIFIED WITH CALCIUM-PHOSPHORUS SALT - AD, Ajagbe; SO, Aribido (Innovare Journal of Agricultural Sciences, 2021)
Objective: This study was conducted to determine nutrient intake of growing West African Dwarf goats fed different dietary models of ensiled cassava peel meal fortified with Calcium-Phosphorus salt mix. Methods: Twenty (20) growing West African Dwarf female goats aged 6–8 months with an initial weight of 8.2 kg ± 0.25 were used for the study. They were randomly allotted to four dietary treatments with five goats per treatment in a completely randomized design. The dietary treatments were Diet 1 (block), Diet 2 (crunchy), Diet 3 (pellet), and Diet 4 (mash). Results: Results obtained indicated that dry matter intake ranged from 466.18 g/d to 575.53 g/day with significantly (p<0.05) higher value in pellet model while crude protein intake was higher in mash model than other treatments. Ether extract and crude fiber intake values were higher 40.13 g/day and 148.08 g/day in pellet feed model. Ash intake ranged from 61.32 g/day to 95.86 g/day. Block and crunchy models had significantly (p<0.05) higher value for ash intake while values obtained for nitrogen-free extract intake was also higher (p<0.05) in pellet model 22.62 g/day than other models. Values of fiber fractions intake obtained were significantly (p<0.05) influenced by dietary models with higher values for neutral detergent fiber, acid detergent fiber and hemicellulose in mash while acid detergent lignin was significantly (p<0.05) for pellet model. Conclusion: It can be concluded that supplementing goat diets with different dietary models of ensiled cassava peel meal fortified with Calcium- Phosphorus salt mix can boost intake of goats for better productive performance and productivity.